2002
DOI: 10.1152/ajpcell.00204.2002
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate 172, essential for modulation of L247T α7 ACh receptors by Ca2+, lines the extracellular vestibule

Abstract: . These permeant divalent cations interact with slowly desensitizing L 247 T ␣7 nAChRs to increase the potency and maximal efficacy of ACh, increase the efficacy of dihydro-␤-erythroidine (DH␤E), and increase agonistindependent activity. Mutation of glutamate 172 (E 172 ) to glutamine or cysteine eliminated these effects of permeant divalent cations. 2-(Trimethylammonium)ethyl methanethiosulfonate (MTSET), a cysteine-modifying reagent directed at water-accessible thiols, inhibited ACh-evoked currents of E 172 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…To test whether this site was involved in the activation by divalent cations of K 144 C/T 198 C ␣7 AChR, we constructed ␣7 receptors with Glu 172 mutated to glutamine in addition to K 144 C and T 198 C mutations. This construct displays an ACh dose-response relationship similar to that seen previously in the E 172 Q mutant (Eddins et al, 2002b) but shows no divalent-activated current (Fig. 4).…”
Section: Single Cysteine Mutations Insupporting
confidence: 72%
See 1 more Smart Citation
“…To test whether this site was involved in the activation by divalent cations of K 144 C/T 198 C ␣7 AChR, we constructed ␣7 receptors with Glu 172 mutated to glutamine in addition to K 144 C and T 198 C mutations. This construct displays an ACh dose-response relationship similar to that seen previously in the E 172 Q mutant (Eddins et al, 2002b) but shows no divalent-activated current (Fig. 4).…”
Section: Single Cysteine Mutations Insupporting
confidence: 72%
“…We included the mutation in the M2 transmembrane domain leucine 247 (L 247 T; L9ЈT) because of its large current amplitudes and nondesensitizing kinetics compared with wild-type ␣7 receptors (Revah et al, 1991). All mutations were introduced into chick ␣7 cDNA by site-directed mutagenesis using the QuikChange method (Stratagene, La Jolla, CA) as described previously (Eddins et al, 2002b) and were confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Mutation at the L9Ј position enhances our ability to measure modification kinetics for cysteine replacements in which the ACh-evoked current amplitudes are attenuated (Beene et al, 2002). All mutations were introduced by site-directed mutagenesis using the QuikChange method (Stratagene, La Jolla, CA) as described previously (Eddins et al, 2002) and were confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Currents were low pass-filtered at 50 Hz and sampled at 100 Hz. Agonist dose-response curves were obtained as described previously (Eddins et al, 2002), and data were fit to the Hill equation using Origin software (OriginLab Corp, Northampton, MA).…”
mentioning
confidence: 99%
“…The amino acid position 172 in the extracellular domain was initially identified by Galzi et al (1996) as the site of action for the calcium modulation, an observation further supported by subsequent sitedirected mutagenesis studies (Eddins et al, 2002;McLaughlin et al, 2006). In contrast, little information is available about the site of modulation by molecules such as IVM, 5-HI, NS-1738, PNU-120596, or other PAMs.…”
mentioning
confidence: 96%